Campylobacter fetus bacteraemia in a peritoneal dialysis patient Bacteriémia - Gouveia,Rita (2014)
Infection is one of the major causes of mortality and morbidity in dialysis patients. Dialysis patients appear to be predisposed to infection due to alterations in primary host defence, advanced age and the presence of comorbid conditions, malnutrition and invasive dialysis procedures. Bacteraemia is seldom a manifestation of infection in peritoneal dialysis patients and is usually secondary to catheter-associated peritonitis. Campylobacter fetus, unlike more common isolates of the same genus, is usually grown from blood samples, without accompanying enteritis, in patients with serious underlying conditions. The authors present a case of Campylobacter fetus bacteraemia in a peritoneal dialysis patient.